Knowledge vis a vis Adoption of Agrithorti System in Doda District of Jammu & Kashmir State - Nain, M.S.; Chandel, S.S. (Indian Journal of Extension Education, 2013)
Raising the purchasing power of people in rural areas has largely to be achieved through agricultural sector, in which  horticultural crops have to play an important role. Adoption of agri-horti system and the factors associated need to be  viewed in totality which calls for the empirical evidences regarding the knowledge and adoption levels of farmers to  achieve the goal of enhanced productivity and profitability. The present study conducted in Doda district of J&K state  highlights that the farmers were having low to medium level of knowledge and adoption of various areas of agri-horti  farming system. The study indicated that the extent of adoption of most of the scientific practices was moderate to low.  The study indicated that the adoption of scientific practices in agri-horti system were associated with respective  knowledge levels of farmers. Enhancement of knowledge of farmers through appropriate methods of scientific principles  with description and explanation of processes and causal relationships will go a long way in addressing the problem of low  adoption of scientific packages in agri-horti system.
Keywords: Agri horti system; adoption; knowledge level; scientific practices; field crops; horticultural crops